Diversification of Pinus halepensis forests by sowing Quercus ilex and Quercus pubescens acorns: testing the effects of different vegetation and soil treatments - Prévosto, Bernard; Monnier, Yogan; Ripert, Christian; Fernandez, Catherine (European Journal of Forest Research, 2010)
The goal of this study was to develop management strategies favouring establishment and survival of holm oak (Quercus ilex L.) and downy oak (Quercus pubescens Willd.)—two species co-occurring in Southern France—in mature Allepo pine forests (Pinus halepensis Mill subsp. halepensis). An experimental design was assessed in a partially cut mature stand of Aleppo pine in which ﬁve soil and vegetation treatments—chopping, chopping followed by scariﬁcation in one or two directions, prescribed burning, control—and two slash treatments (presence/absence) were applied. A total of 1,600 sowing points, each composed of 3 Q. ilex or Q. pubescens acorns, were installed in the different treatments in November of two consecutive years at 6 and 18 months, after the end of treatments. Survival was monitored 3 and 2 years after sowing, soil surface at the sowing points was characterized at different dates, and predawn leaf water potentials were measured during the dry season. High mortality occurred after the ﬁrst summer, but survival after 1 year was 2.3–5.2 higher in Q. ilex than in Q. pubescens, conﬁrming that Q. ilex was better adapted to the drier parts of the Mediterranean area. Survival was signiﬁcantly inﬂuenced by the treatments, but there was a variable response between the two sowing years under most of the treatments. Only intense ﬁre proved the most beneﬁcial treatment for seedling survival in both years. The micro-local soil cover conditions induced by the treatments played a major role in explaining oak survival. In particular, grass cover (mainly Brachypodium retusum) proved to be largely unfavourable to seedling survival and growth, and this detrimental effect was also conﬁrmed by lower predawn leaf water potential values with increasing grass cover. Acorn introduction designed to diversify mature Aleppo pine forest after soil and vegetation treatments therefore has to be considered for treatments that most efﬁciently impair the pre-existing competing grass cover such as prescribed high-intensity ﬁre treatment.
Keywords: mediterranean oaks; Prescribed burning; seedling growth; seedling survival; Stand regeneration; Vegetation control

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

Between-tree variations in leaf Î´ 13 C of Quercus pubescens and Quercus ilex among Mediterranean habitats with different water availability - Damesin, C; Rambal, S; Joffre, R (Oecologia, 1997)
In this study, sun leaf carbon isotope compo- sition (d 13 C) of two co-occurring woody Mediterranean species (Quercus pubescens Willd., a deciduous oak, and Q. ilex L., an evergreen one) was investigated on four sites with dierent water availability. The total range of d 13 C values was 4.4 and 3.1& for Q. pubescens and Q. ilex respectively. The intra-site variability was about 3&. Total mean per species was equal. There were sig- ni®cant dierences among sites, but at each site means of d 13 C were not signi®cantly dierent between species. A simple physiological model predicts no dierence in in- trinsic water-use eciency (WUEi ) between evergreen and deciduous oaks. The relationship between site means of d 13 C and water parameters suggests that there is a leaf functional adjustment with respect to available water resource. No correlation was found between d 13 C and the contents of any mass-based biochemical cons- tituent. Nevertheless there was a signi®cant correlation between d 13 C and leaf mass per area of Q. ilex. For both species, there is also a positive correlation between leaf d 13 C and individual crown area, i.e. a structural char- acteristic at tree level. Causal relations between d 13 C and plant-environment interactions are discussed.
Keywords: carbon isotope composition; Foliar chemical constituents; mediterranean oaks; tree structure; Water availability

TEMPERATURE RESISTANCE AS AN ECO-PHYSIOLOGICAL CHARACTERISTIC OF PLANTS .1. QUERCUS-ILEX AND OTHER MEDITERRANEAN OAKS - LARCHER, W; MAIR, B (OECOLOGIA PLANTARUM, 1969)
APS
Keywords: eco-physiology; mediterranean oaks; Quercus ilex; temperature resistance